Green marketing strategies for sustainability development of firm's performance in Malaysia: for green economy. (29th June 2020) - Supaat, Siti Hindun; Ahamat, Amiruddin; Nizam, Nurul Zarirah
This manuscript goals to explain and refine the relationship of green marketing strategies between environmental culture, eco-orientation, green promotion, green innovation and corporate social responsibility towards firm's performance for sustainability development to green economy. Given the relevance of green marketing strategies to the success of a sustainability business, the emphasis on green marketing strategies and its effect on profitability to the green economy in future are inadequate. This research tackles the breach by offering a full view of tactical green marketing strategies and its competitive advantage. Specifically, the findings draw on contemporary green marketing literature indicate that an essential interaction exists among strategy and industrial people which increases the competitive advantage for humankind and the ecosystem. This work usages an updated methodology to draw on the present literature on the motorists and outcomes of strategic green marketing for the success of the sustainable development firm's performance.